Talent identification - Burgess, R.
It is clear that talent identification is a diverse subject that is not easily summed up. There are many different views on what talent identification accomplishes and how it should be structured. While the resources needed to implement programs similar to those undertaken in the G.D.R. are not available to many countries in the 90's this does not mean that talent identification would not be worthwhile. By linking talent identification to the already existing school system results can still be achieved in talent identification.